Makna Biaya Dalam Tradisi Antar Harta (Dutu) Dilihat Dari Sudut Pandang Akuntansi - Siti Magfira Rahmatia Lahay; Tri Handayani Amaliah; Ayu Rakhma Wuryandini (Economics and Digital Business Review, 2024)
The results of this research show that the meaning of costs in the "Dutu" inter-property tradition is as a form of transaction, as budgeting and planning, costs as sincerity, costs as a symbol of commitment, and is interpreted by the community as symbolic and traditional as well as sacrifice. This shows that costs have more value than just the goal of gaining financial profit or income, but have a deeper meaning when viewed from a cultural perspective. From the Dutu tradition, it can be concluded that Tulus Ikhlas is a strong basis for interpreting costs. With sincerity, the costs incurred become more than just numbers on an accounting sheet; it is an expression of affection, appreciation and sincere commitment in living life together.